The concept of «Chinese women» the backdrop of the global linguistic image. - Kenzhebaeva., A. A. (Journal of Oriental Studies, 2016)
It is considered in the article the concept of «Chinese women» as a fragment of the Chinese language picture of the world(in the faceof the world). At the present stage of development of linguistics dominant thinking’s not only knowledge, but also understanding that inevitably leads to the study of the interaction of language, culture and identity.